Methodology of calculation and structural analysis of Journal Impact Factor based on the Web of Science: A case study of Nature - Liu, Xue-Li; Gai, Shuang-Shuang; Zhang, Shi-Le; Liu, Xue-Li; Gai, Shuang-Shuang; Zhang, Shi-Le (Malaysian Journal of Library and Information Science, 2016)
In this paper, we take Nature as a case study to present a new method for calculating and analyzing the structure of the Impact Factor (IF) using the Web of Science (WoS) database and the definition of IF. We calculated Nature’s IF for 2013 using data retrieved on 21 March 2014 from the WoS database and comprehensively analyzed its structural features, thereby identifying the contributions to Nature’s IF for 2013 of different document types, highly cited papers, highly cited authors, different institutions, and different countries and regions. The results show: (a) the calculated value of Nature’s IF for 2013 is 41.002 according to data retrieved in March of 2014; (b) two types of document, article and review, made prominent contributions to Nature’s IF for 2013, with contribution values of 35.338 and 3.179, respectively; (c) the institutions that made the greatest contributions to Nature’s IF for 2013 are mainly located in the USA and England, with the first three highly cited institutions being Harvard University, Stanford University, and Washington University; (d) the contributions of different countries and regions to Nature’s IF for 2013 differ greatly, with the combined contribution rate of the USA and England being 70.4 percent.